Differential gene expression of the healthy conjunctiva during the day - Alenezi, Heba; Ozkan, Jerome; Willcox, Mark; Parnell, Grant; Carnt, Nicole (Contact lens & anterior eye, 2022)
To determine if there is diurnal variation in gene expression in normal healthy conjunctival cells. Bulbar conjunctival swab samples were collected from four healthy subjects in the morning and evening of the same day. The two swab samples were taken from one eye of each participant, with a minimum of five hours gap between the two samples. RNA was extracted and analysed using RNA sequencing (RNA-Seq). A total of 121 genes were differentially expressed between the morning and the evening conjunctival samples, of which 94 genes were upregulated in the morning, and 27 genes were upregulated in the evening. Many of the genes that were upregulated in the morning were involved in defence, cell turnover and regulation of gene expression, while the genes upregulated in the evening were involved in signalling and mucin production. This study has identified several genes whose expression changes over the course of the day. Knowledge of diurnal variations of conjunctival gene expression provides an insight into the regulatory status of the healthy eye and provides a baseline for examining changes during ocular surface disease.